Altered dynamics of lipid metabolism in muscle cells from patients with idiopathic inflammatory myopathy is ameliorated by 6 months of training - Nemec, M; Vernerová, L; Laiferová, N; Balážová, M; Vokurková, M; Kurdiová, T; Oreská, S; Kubínová, K; Klein, M; Špiritović, M; Tomčík, M; Vencovský, J; et al. (Journal of physiology (London. Print), 2021)
KEY POINTS: Regular exercise improves muscle functional capacity and clinical state of patients with idiopathic inflammatory myopathy (IIM). In our study, we used an in vitro model of human primary muscle cell cultures, derived from IIM patients before and after a 6-month intensive supervised training intervention to assess the impact of disease and exercise on lipid metabolism dynamics. We provide evidence that muscle cells from IIM patients display altered dynamics of lipid metabolism and impaired adaptive response to saturated fatty acid load compared to healthy controls. A 6-month intensive supervised exercise training intervention in patients with IIM mitigated disease effects in their cultured muscle cells, improving or normalizing their capacity to handle lipids. These findings highlight the putative role of intrinsic metabolic defects of skeletal muscle in the pathogenesis of IIM and the positive impact of exercise, maintained in vitro by yet unknown epigenetic mechanisms. ABSTRACT: Exercise improves skeletal muscle function, clinical state and quality of life in patients with idiopathic inflammatory myopathy (IIM). Our aim was to identify disease-related metabolic perturbations and the impact of exercise in skeletal muscle cells of IIM patients. Patients underwent a 6-month intensive supervised training intervention. Muscle function, anthropometric and metabolic parameters were examined and muscle cell cultures were established (m. vastus lateralis; Bergström needle biopsy) before and after training from patients and sedentary age/sex/body mass index-matched controls. [14 C]Palmitate was used to determine fat oxidation and lipid synthesis (thin layer chromatography). Cells were exposed to a chronic (3 days) and acute (3 h) metabolic challenge (the saturated fatty acid palmitate, 100 μm). Reduced oxidative (intermediate metabolites, -49%, P = 0.034) and non-oxidative (diglycerides, -38%, P = 0.013) lipid metabolism was identified in palmitate-treated muscle cells from IIM patients compared to controls. Three days of palmitate exposure elicited distinct regulation of oxidative phosphorylation (OxPHOS) complex IV and complex V/ATP synthase (P = 0.012/0.005) and adipose triglyceride lipase in patients compared to controls (P = 0.045) (immunoblotting). Importantly, 6 months of training in IIM patients improved lipid metabolism (CO2 , P = 0.010; intermediate metabolites, P = 0.041) and activation of AMP kinase (P = 0.007), and nearly normalized palmitate-induced changes in OxPHOS proteins in myotubes from IIM patients, in parallel with improvements of patients' clinical state. Myotubes from IIM patients displayed altered dynamics of lipid metabolism and impaired response to metabolic challenge with saturated fatty acid. Our observations suggest that metabolic defects intrinsic to skeletal muscle could represent non-immune pathomechanisms, which can contribute to muscle weakness in IIM. A 6-month training intervention mitigated disease effects in muscle cells in vitro, indicating the existence of epigenetic regulatory mechanisms.
Keywords: Myositis; metabolismus lipidů; myozitida; kosterní svaly; kvalita života; kosterní svalová vlákna; lidé; Lipid Metabolism; Muscle Fibers, Skeletal; Quality of Life; Muscle, Skeletal; Humans